(untitled) (Politeja, 2019)
On some Actual Aspects of the Interpretation of the Liberal Tradition in Russia The article examines the key moments of the transformation of liberal tradition in Russia in the context of analysis of the main directions of the transformation of liberal ideological discourse and liberal culture in Western Europe and the United States. The need for such an analysis is primarily determined by the fact that since the early 1990s Western liberal stereotypes have become an ideological basis of the new Russian political elite and the dominant trend in state propaganda. However, the following main fact is often overlooked: in the 20th century,Russian liberalism was compromised twice, so in the short-term the hopes for the revival of the liberal ideas are gone. In the West, the liberal tradition has also been in the state of crisis: Western liberalism has been undergoing a very significant transformation that has far-reaching cultural and political implications. In particular, at the turn of the 21st c., a more active role in Western public discourse was taken by the radical neo-conservative versions of an ideology that combined a conservative program of political reforms with a strong libertarian (neoliberal) rhetoric. This ideology is actively used by the ruling circles of the US and Western Europe to influence ideologically the political elites of Russia – as it happened in Central and Eastern Europe during the so-called “velvet revolutions”. At the same time, what increasingly clearly and sharply came to the fore in the late twentieth century is anti-liberal thought and criticism that has always evolved in parallel with liberalism itself and that almost never ceases to exist.